(untitled) (Analysis in Theory and Applications, 2016)
Let ΩL^2(S^n-1) be homogeneous function of degree zero and b be BMO functions. In this paper, we obtain some boundedness of the Littlewood-Paley Operators and their higher-order commutators on Herz spaces with variable exponent.